Proinflammatory Cytokines Correlate with Depression and Anxiety in Colorectal Cancer Patients - Miranda, Diego Oliveira; Soares de Lima, Tais Aparecida; Azevedo, Lucas Ribeiro [UNESP]; Feres, Omar; Ribeiro da Rocha, Jose Joaquim; Pereira-da-Silva, Gabriela (Hindawi Publishing Corporation, 2014)
The objective of this study was to investigate whether serum cytokine levels correlate with depression and anxiety in colorectal cancer (CRC) patients. Twenty patients hospitalized for surgical resection of CRC were included in the study group and twenty healthy volunteers comprised the control group. Depression and anxiety were analyzed using the Hospital Anxiety and Depression Scale (HADS), and serum levels of IL-1 beta, IL-6, IL-8, IL-10, IL-12, TNF-alpha, and TGF-beta were measured by Cytometric Bead Array. We found that more than half of CRC patients presented clinically significant levels of anxiety or depression, and 65% of them manifested a combination of severe anxiety and depression. CRC patients had increased serum levels of IL-1 beta, IL-6, IL-8, and TNF-alpha but lower IL-10 concentrations. Correlation analysis between HADS score and cytokine levels revealed a positive association of anxiety and/or depression with IL-1 beta, IL-6, IL-8, and TNF-alpha and a negative correlation with IL-10. These results indicate that circulating proinflammatory cytokines are involved in the pathophysiology of anxiety and depression in CRC patients. A better understanding of the molecular mechanisms involved in these psychological disorders will allow the design of therapeutic interventions that lead to an improved quality of life and overall survival of CRC patients.